Nutritional valorization of Manila tamarind accessions through antioxidant analysis and UHPLC-Q-TOF-MS-based metabolomic profiling - Yadav, Ashok; Jha, Suchisree; Choudhary, Girija; Ram, Asha; Kumar, Rajeev; Kumar, Naresh; Anuragi, Hirdayesh; Garg, Sandeep; Kumar, Anil; Singh, Pradyuman; Dwivedi, Raghunandan Prasad; Arunachalam, Ayyanadar; et al. (Frontiers in Nutrition, 2025)
IntroductionManila tamarind is an underutilized and multipurpose crop with considerable value for food, fodder, fuel, and green manuring. Its hardy nature, drought tolerance, and diverse applications make it a promising climate-smart crop for agroforestry systems, especially in the drylands of the Bundelkhand region. However, research on its antioxidant potential and phytochemical composition has been largely neglected.MethodsTo address this gap, the present study was conducted to assess the antioxidant content and identify health-related phytochemicals in the arils of 15 different Manila tamarind accessions, which were collected locally from the Bundelkhand region. Antioxidant analysis (DDPH, ABTS, Metal Chelating), phenol, flavonol, and anthocyanin were estimated as per standard procedures, whereas the phytochemicals were estimated through UHPLC-Q-TOF-MS analysis.ResultsThe results revealed significant variation in vitamin content (vitamin A: 0.18–0.28 mg/100 g, thiamin: 0.18–0.24 mg/100 g, riboflavin: 0.11–0.18 mg/100 g, vitamin C: 122–139 mg/100 g, and b-carotenoid equivalent 11.4–19.6 mg/100 g) and antioxidant activity across various assays, including DPPH (65.58–282.44 mg/ml), ABTS (117.80–508 IC50 mg/ml), metal chelating capacity (167.41–376.06 IC50 mg/ml), total phenolic content (0.019–0.174 mg GAE/g fresh weight), and total flavonol content (0.0042–0.0088 mg QE/g fresh weight). Anthocyanin levels ranged from 0.126 to 0.262 mg TAC/g fresh weight. Phytochemical profiling led to the identification of 144 compounds, which were classified into 43 biological function categories. The predominant compounds exhibited antioxidant, anti-inflammatory, anticancer, neuroprotective, antifungal, antibacterial, antimicrobial, antiviral, anti-tumor, analgesic, cardioprotective, and antidiabetic properties, highlighting the crop's immense potential for health and nutritional applications.ConclusionThe primary aim of this study was to evaluate the potential of this plant, and the findings provide strong evidence that this plant possesses significant bioactive compounds, suggesting its potential use in combating a range of infectious diseases. In addition to this, the findings of this study are valuable for selecting superior parent lines to enhance desirable traits in future Manila tamarind breeding programs.